Ceroid granulomas in the female genital system. Issue 11 (November 1995) - Ooi, K; Riley, C; Billson, V; Ostör, A G
Abstract : Three cases of ceroid granulomas of the female genital system are presented, involving the cervix in two and lesions in the ovaries and bowel serosa in the other. Ceroid granulomas are unusual and interesting lesions formed when suitable substrates accumulate within macrophages to such an extent that a relative lack of biological antioxidants results and auto-oxidation and conversion to ceroid is favoured. This may occur in the setting of haemorrhage and necrosis, whether from tumour necrosis or associated with endometriosis. Other sources of lipids and lipoproteins include bile, meconium and vernix caseosa.